Meningkatkan Imunitas Tubuh Melalui Senam Umum di Masa New Normal - Iman Rubiana; Fegie Rizkia Mulyana; Melya Nur Herliana; Novi Soraya (Jurnal Pengabdian Olahraga Masyarakat (JPOM), 2022)
The results of interviews between the service team and local residents obtained problems and residents' wishes to be facilitated and given activities and education that can increase activities and immunity of residents, especially by exercising in the new normal. Various busy residents and work pressures that result in mental disorders. The psychological impact felt by residents will increase if it is not balanced with immunity or the degree of body fitness. So there is a need for an understanding of new activities in the New Normal and the importance of increasing body immunity in the New Normal by exercising properly and correctly. The purpose of this service activity is to provide socialization and education related to adapting new habits and how to exercise properly and correctly in order to increase body immunity in the New Normal. The implementation method used in this service activity uses the lecture method and socialization by doing mass gymnastics for 20 meetings which are held every Sunday. The results of this service activity are that residents feel positive impacts such as getting used to a clean and healthy living culture, increasing citizens' insight regarding how to exercise properly and correctly according to the FITT formula (Frequency, Intensity, Time, and Type), increasing residents' motivation is shown by the enthusiasm of residents to follow mass gymnastics activities during service activities, as well as the creation of a culture of exercising once a week guided by one of the residents who was given education during the service activity.AbstakHasil wawancara antara tim pengabdian bersama warga setempat didapat permasalahan serta keinginan warga untuk difasilitasi dan diberikan kegiatan serta edukasi yang bisa meningkatkan aktivitas serta imunitas warga khususnya dengan berolahraga dimasa new normal. Berbagai kesibukan warga dan tekanan pekerjaan yang mengakibatkan gangguan mental. Dampak psikologis yang dirasakan warga akan semakin meningkat apabila tidak diimbangi dengan kekebalan ataupun derajat kebugaran tubuh. Sehingga perlunya pemahaman terkait aktivitas baru dimasa New Normal dan pentingnya meningkatkan imunitas tubuh dimasa New Normal dengan cara berolahraga yang baik dan benar. Tujuan dari kegiatan pengabdian ini, memberikan sosialisasi dan edukasi terkait adaptasi kebiasaan baru dan cara berolahraga yang baik dan benar guna meningkatkan imunitas tubuh dimasa New Normal. Metode pelaksanaan yang digunakan dalam kegiatan pengabdian ini menggunakan metode ceramah dan sosialisasi dengan melakukan senam secara masal selama 20 kali pertemuan yang dilaksananakan setiap hari minggu.  Hasil  dari  kegiatan  pengabdian ini  yaitu warga merasakan dampak positif seperti membiasakan budaya hidup bersih dan sehat,bertambahnya wawasan warga terkait cara berolahraga yang baik dan benar menurut rumus FITT (Frekuensi, Intensitas, Time, dan Tipe), bertambahnya motivasi warga ditunjukkan dengan animo warga mengikuti kegiatan senam massal selama kegiatan pengabdian berlangsung, serta terciptanya budaya berolahraga setiap satu minggu satu kali dengan dipandu oleh salah satu warga yang diberikan edukasi selama kegiatan pengabdian berlangsung